Immunoglobulin G antibodies against Porphyromonas gingivalis or Aggregatibacter actinomycetemcomitans in cardiovascular disease and periodontitis. Issue 1 (1st January 2017) - Damgaard, Christian; Reinholdt, Jesper; Enevold, Christian; Fiehn, Nils-Erik; Nielsen, Claus Henrik; Holmstrup, Palle
ABSTRACT: Objectives: The aim was to elucidate whether levels of circulating antibodies to Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis correlate to loss of attachment, as a marker for periodontitis and cardiovascular disease (CVD). Design: Sera were collected from 576 participants of the Danish Health Examination Survey (DANHES). Immunoglobulin G antibodies against lipopolysaccharide (LPS) and protein antigens from the a, b and c serotypes of A. actinomycetemcomitans and P. gingivalis were quantified by titration in ELISA plates coated with a mixture of antigens prepared by disintegration of bacteria. Results: Levels of antibodies against P. gingivalis (OR = 1.48) and A. actinomycetemcomitans (1.31) associated with periodontitis, as determined by univariable logistic regression analysis. These antibody levels also associated with CVD (1.17 and 1.37), respectively, However, after adjusting for other risk factors, including age, smoking, gender, alcohol consumption, overweight, and level of education using multivariable logistic regression analysis, only increasing body mass index (BMI; 1.09), previous smoking (1.99), and increasing age (decades) (2.27) remained associated with CVD. Increased levels of antibodies against P. gingivalis (1.34) remained associated with periodontitis after adjusting for other risk factors. Conclusions: CVD and periodontitis were associated with levels of IgG antibodies to P. gingivalis or A. actinomycetemcomitans in univariable analyses, but only the association of P. gingivalis antibody levels with periodontitis reached statistical significance after adjustment for common confounders. Age, in particular, influenced this relationship.